PENGARUH ATMOSPHERIC TERHADAP BEHAVIORAL INTENTION DENGAN VARIABEL SERVICE QUALITY SEBAGAI INTERVENING STUDI EMPIRIS PADA RESTORAN DI DAERAH MENTENG - Halim, Stephanie (Jurnal Manajemen, 2015)
This study examines the behavioral intention of respondents who have been to Lara Djonggrang restaurant, Menteng, Jakarta, a restaurant serving typical Indonesian food themed with the legend of Central Java, which is the story of Lara Djonggrang. The study was conducted to determine the factors that affect behavioral intentions while atmospheric serves as independent variable and service quality as mediation variable. The analysis technique used in this study is the PLS (Partial Least Square). The results shows that Atmospheric has an effect on Service Quality. Atmospheric also has an effect on Behavioral Intention. Service Quality has an effect on Behavioral Intention.